Anti-vaxxers : how to challenge a misinformed movement - Berman, Jonathan M. (Cambridge, Mass. The MIT Press, 2020)
Vaccines are a documented success story, one of the most successful public health interventions in history. Yet there is a vocal anti-vaccination movement and the propagation of anti-vax claims through books, documentaries, and social media. In Anti-vaxxers, Jonathan Berman explores the phenomenon of the anti-vaccination movement, recounting its history from its nineteenth-century antecedents to today's activism, examining its claims, and suggesting a strategy for countering them. --
"A presentation of the scientific argument in favor of vaccination, which probes the consequences, origins and impact of the anti-vaccination movement"--
Is there even a problem? -- Understanding vaccines -- The world before vaccines -- The first vaccine -- The first anti-vaccine movements -- Vaccine pioneers -- The twentieth-century anti-vaccine movement -- Autism -- The anti-vaccine movement 1998-present -- Vaxxed -- Too many, too soon -- Deadly immunity -- Ineffective "alternatives" to vaccination -- Social media, "fake news," and the spread of information -- Escalation of commitment -- Religion and vaccine hesitancy -- Big pharma -- Anti-vaccine activism in 2018 and 2019 -- Vaccine advocates -- Who are they? -- The anti-vaccine parent -- What changes minds about vaccines?
Includes bibliographical references (p.217-271) and index.
Keywords: Anti-vaccination movement; Vaccines; Vaccination refusal